(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the popularity of mobile technologies, their active participation in all areas of our lives, the penetration of mobile technologies into education, trade, politics, entertainment and other areas of human life, the importance of mobile applications in the educational process and their importance in improving the efficiency of the educational process, the use mobile devices in the educational process, it is noted that this helps to increase motivation, develop independent learning skills. Scientific thoughts of Alan Key, Y. Eremin, E. Krylov, examples from the works of M. Ragus, M. Sharples, Mohammed Aliy and other scientists are given. It was noted about the scientific research of Uzbek scientists in this area. The use of multimedia in mobile learning and the acceleration of information exchange, the use of mobile technologies, the flexibility of mobile devices in an individual approach, taking into account the personal psychological and physiological characteristics of students, are given. In order to build a digital Uzbekistan, laying its first foundation, proposals were made to use digital technologies - mobile technologies in the educational process, create their own national mobile applications and implement them in class activities, improve class efficiency.